Revitalisasi Kepemimpinan Untuk Meningkatkan Mutu Pendidikan Madrasah - Abrori, Husnan (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
There are no stupid people; there are people who do not know or are late to know. It is best for leaders to humanize humans, provide motivation, give opportunities for creativity to emerge, cultivate them according to their capacity so that innovation and their imagination do not sleep. A good leader will not look for mistakes blindly, or blame in public. Angry in public is killing human characters. The implication is that they will be quiet and lazy to innovate because there is no appreciation. So that they just become obedient and say it's up to the leader. Leaders who are imprisoned in respect and appreciation only will feel happy to be respected and respected even though it is another name for the sleeping of subordinate creativity. The worse is the top down instruction model leader who is an admirer of the institutional hierarchy who places a leader as the highest authority in the management area, so he always feels right, and taboo to be criticized and blamed. Apologies, ask for help, thank you for never coming out in verbal linguistics. There are only procedures, concepts, rigid instructions that are haram to be criticized. Therefore it is necessary to revitalize leadership in the madrasa.